The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.nucmedbio.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting aldehyde dehydrogenase: a potential approach for cell labeling

Abstract: Introduction-To advance the science and clinical application of stem cell therapy, the availability of a highly sensitive, quantitative, and translational method for tracking stem cells would be invaluable. Because hematopoetic stem cells express high levels of the cytosolic enzyme aldehyde dehydrogenase-1A1 (ALDH1), we sought to develop an agent that is specific to ALDH1 and thus to cells expressing the enzyme. Such an agent might be also helpful in identifying tumors that are resistant to cyclophosphomide ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition, attempts at in vivo stem cell labeling have employed ALDH radiolabeled substrates. However, the resultant charged compounds were not polar enough to be retained into the cells [ 59 ].…”
Section: Aldh As a Marker For Cancer Stem Cellsmentioning
confidence: 99%
“…In addition, attempts at in vivo stem cell labeling have employed ALDH radiolabeled substrates. However, the resultant charged compounds were not polar enough to be retained into the cells [ 59 ].…”
Section: Aldh As a Marker For Cancer Stem Cellsmentioning
confidence: 99%
“…The degree of trapping is particularly challenging to control as those two compounds initially stained cells but failed to accumulate. Vaidyanathan et al reported two radiolabeled ALDH substrates that could be converted into the acid form by the purified enzyme 25 . Both substrates, however, failed to accumulate inside of cells with high ALDH activity when compared with the DEAB control.…”
Section: Discussionmentioning
confidence: 99%
“…Since early detection of cancer is key for curative treatment, there is considerable interest in noninvasive and inexpensive cancer diagnosis. Targeting ALDH as a potential approach for cancer cell labeling might be an appropriate “tracer” for discerning drug-sensitive and drug-resistant phenotypes of cancers to evaluate the effectiveness of novel therapies ( 27 ). Ultimately, targeted killing of a cell, based upon its specialized metabolic state (here ALDH activity), may be useful for clinical application to preferentially target those rapidly proliferating cells for growth inhibition or death, as has been described in the case of threonine dehydrogenase in mouse embryonic stem cells ( 1 ).…”
Section: Additional Benefits Of Considering New Aldh Substratesmentioning
confidence: 99%